A Integration of 7E teaching methods into the management of teaching and learning about gas exchange and plants dehydration at Luang Prabang Teachers Training College, academic year 2019 - 2020 - CHITTAPHONE , Vilayphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The objectives of this research were to compare learning outcomes, to study the student achievement index and to study the students' satisfaction with the management of teaching-learning on gas exchange and plants dehydration by deploying 7E teaching methods in the second semester of the 2019-2020. 30 participants were selected as samples including 15 females. In this study, there are three key instruments were used to collect information, for instance, lessons, quizzes and student satisfaction questionnaires. The results are as follows: students 'learning outcomes for pre - teaching averaged 4.06/10 and post-teaching averaged 9.23 / 10, (p <0.05) (t = 31.37), the 7E explicit teaching method with EI = 0.52> 0.50 and students' satisfaction with the management of teaching and learning the students' satisfaction was at the highest level of satisfaction.